2013
DOI: 10.1007/978-1-62703-348-0_2
|View full text |Cite
|
Sign up to set email alerts
|

A New Chemical Approach to the Efficient Generation of Mouse Embryonic Stem Cells

Abstract: Here, we present a highly efficient and reproducible method for the establishment of mouse embryonic stem cells (mESCs) from embryonic day 3.5 (E3.5) whole blastocysts. This protocol involves the use of small molecules SB431542 and PD0325901, which inhibit transforming growth factor-β (TGF-β) and extracellular signal-regulated kinases (ERK1/2), respectively. This protocol is universal in the derivation of mESC lines from NMRI, C57BL/6, BALB/c, DBA/2, and FVB/N strains, which have previously been considered ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Mouse embryonic derivative stem cell line, RoyanB20, was used in this study and retained in an undifferentiated state as described (Baharvand and Hassani 2013). Cells were cultured in serum free medium, a mixed cocktail of Dulbecco's modified Eagle medium/Ham's-Nutrient Mixture F-12 (DMEM F12) with Neurobasal media (Gibco, USA) supplemented with 0.5% BSA, 2 mM glutamine, 0.1 mM nonessential amino acids, 1% penicillin-streptomycin (all from Invitrogen, USA), 0.1 mM β-mercaptoethanol (Sigma-Aldrich, USA) and 1000 U/mL leukemia inhibitory factor (LIF; Chemicon, USA), 1 μM PD0325901(Sigma, USA) and 10 μM SB431542 (Sigma, USA),1% N2 (Gibco, USA) , 2% B27 (Gibco, USA).…”
Section: Mescs Culture and Neural Differentiation Stagesmentioning
confidence: 99%
“…Mouse embryonic derivative stem cell line, RoyanB20, was used in this study and retained in an undifferentiated state as described (Baharvand and Hassani 2013). Cells were cultured in serum free medium, a mixed cocktail of Dulbecco's modified Eagle medium/Ham's-Nutrient Mixture F-12 (DMEM F12) with Neurobasal media (Gibco, USA) supplemented with 0.5% BSA, 2 mM glutamine, 0.1 mM nonessential amino acids, 1% penicillin-streptomycin (all from Invitrogen, USA), 0.1 mM β-mercaptoethanol (Sigma-Aldrich, USA) and 1000 U/mL leukemia inhibitory factor (LIF; Chemicon, USA), 1 μM PD0325901(Sigma, USA) and 10 μM SB431542 (Sigma, USA),1% N2 (Gibco, USA) , 2% B27 (Gibco, USA).…”
Section: Mescs Culture and Neural Differentiation Stagesmentioning
confidence: 99%
“…The above studies exploring the use of small molecule compounds on iPSC provided theoretical and technical basis to achieve exogenous gene free livestock naive iPSC. [62]. The recent studies [2] have showed that morphological and biological characteristics of human ES was more similar to the mouse primed epiblast stem cells [counterpart to primed state].…”
Section: Small Molecule Compounds Replaced Transcription Factors For mentioning
confidence: 99%